Multiwavelength behaviour of the blazar 3C 279: decade-long study from gamma-ray to radio - Larionov VM (OXFORD UNIV PRESS, 2022)
We report the results of decade-long (2008-2018) gamma-ray to 1 GHz radio monitoring of the blazar 3C 279, including GASP/WEBT, Fermi and Swift data, as well as polarimetric and spectroscopic data. The X-ray and gamma-ray light curves correlate well, with no delay greater than or similar to 3 h, implying general cospatiality of the emission regions. The gamma-ray optical flux flux relation changes with activity state, ranging from a linear to a more complex dependence. The behaviour of the Stokes parameters at optical and radio wavelengths, including 43 GHz Very Long Baseline Array images, supports either a predominantly helical magnetic field or motion of the radiating plasma along a spiral path. Apparent speeds of emission knots range from 10 to 37c, with the highest values requiring bulk Lorentz factors close to those needed to explain gamma-ray variability on very short time-scales, The Mg II emission line flux in the 'blue' and 'red' wings correlates with the optical synchrotron conlinuum flux density, possibly providing a variable source of seed photons for inverse Compton scattering. in the radio bands, we find progressive delays of the most prominent light-curve maxima with decreasing frequency, as expected from the frequency dependence of the tau = 1 surface of synchrotron self-absorption. The global maximum in the 86 GHz light. curve becomes less prominent at lower frequencies, while a local maximum, appearing in 2014, strengthens toward decreasing frequencies, becoming pronounced at similar to 5 GHz, These tendencies suggest. different Doppler boosting of stratified radio-emitting zones in the jet.